Design English Learning Material Through Video for Housekeeping - Sri Ainun Rukmana; Finny - Anita; maliqul - hafis (Journal of English Language Teaching and Education (JELTE), 2023)
This research uses the Research and Development (R&D) development method to develop video-based learning materials using Canva for Housekeeping materials. As well as checking the suitability of the video through 3 experts, namely media experts, language experts and material experts. The development of video-based teaching materials is guided by the ADDIE model development stages which consist of five main stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The subjects of this research were class XI students at SMK Negeri 5 Pontianak majoring in hospitality, housekeeping subjects. Data collection was carried out using direct communication in the form of semi-structured interviews and indirect communication through questionnaires with the help of a Likert scale. The interview data obtained was then analyzed using the interactive analysis model of Miles and Huberman (2014) to determine students' responses to learning English. During the questionnaire, the data analysis process involved media experts, language experts and material experts using descriptive statistical analysis to obtain the percentage of video suitability in terms of presentation, language and content. Based on the research results, it is known that the development of video media is classified as "very feasible" for use as a learning medium for class XI students in the Hospitality Department. This can be seen from the results of media expert assessments of 89.29%, material expert opinions of 96.43%, language expert opinions of 93.75%.